Pig breeding with royal palm nuts and other palm by-products. Short review - Ly, J.; Ayala, Lázara (Cuban Journal of Agricultural Science, 2018)
A survey was conducted among 200 randomly selected Cuban pig farmers and members of cooperatives in the provinces of Artemisa and Mayabeque, in western Cuba, and Granma, in the east of the country. The survey inquired about practices of palm cultivation and animal husbandry of pigs reared with royal palm nuts, and thus a digital data bank was constituted. A second digital bank was organized with documentation located in internet, on palm tree forestry. Surveys indicated that there was not much empirical knowledge related to the cultivation of royal palms in Cuba. Characteristics of the chemical composition of royal palm nuts make its digestible energy content equivalent to that of maize. However, its richness in insoluble fiber, can negatively influence on voluntary intake of food by pigs especially when the proportion of royal palm nuts in the ration exceeds a third of it. No different responses have been found when the animals are fattened with conventional maize/soybean or non-conventional diets, in which the imported food resources have been partially replaced (30-45 %) by an autochthonous one, royal palm nuts in the form of meal, ground after drying, with the rest of the ingredients of the dietary formula. The implementation of new research projects and technological innovation will allow the design of more complete model of non-conventional pig production in the nonstate cooperative sector, in cooperatives throughout the country, through the training and participation of staff for the empowerment of the new knowledge in the use of royal palm nuts for feeding pigs, along with the generation of new complementary knowledge to those already existing. Key words: pigs, royal palms, forestry, performance traits